(untitled) (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Analysis of the optimal starting modes of the mechanism of trolley movement along the tower crane boom during the steady movement of the slewing mechanism is presented. The optimal movement modes of the trolley movement mechanism obtained in previous studies were determined by minimizing the mean square values of the driving moment of the drive, its first and second derivatives by time. For these modes of movement, the extremals of th load coordinates, which minimize the selected criteria, are determined. For these extremales, the values of the optimization criteria for different durations of the slewing mechanism acceleration were determined. An analysis of the received criteria for the evaluation of the acceleration modes was carried out, from which it was established that the best indicators of the modes are achieved when using the criteria refered to the root-mean-square value of the driving torque rate. The dimensionless values of the criteria for optimized movement modes of the trolley dur- ing steady rotation of the crane were determined. A complex criterion in the form of a linear convolution with weighting coefficients was developed. To assess the impact of extremals on the value of the optimization criteria, a complex dimensionless criterion was used. The numer- ical values of the optimization criteria are confirmed by the results of plots of the driving troque, and its first and second derivatives by time were given.